2018
DOI: 10.1039/c8lc00672e
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of traumatic brain injury using miRNA signatures in nanomagnetically isolated brain-derived extracellular vesicles

Abstract: The accurate diagnosis and clinical management of traumatic brain injury (TBI) is currently limited by the lack of accessible molecular biomarkers that reflect the pathophysiology of this heterogeneous disease. To address this challenge, we developed a microchip diagnostic that can characterize TBI more comprehensively using the RNA found in brain-derived extracellular vesicles (EVs). Our approach measures a panel of EV miRNAs, processed with machine learning algorithms to capture the state of the injured and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 77 publications
0
64
0
Order By: Relevance
“…Studies show that supervised classifier algorithms perform better than unsupervised methods when development of predictive models of injury and future outcome is the goal rather than identification of hidden patterns within the dataset [33]. Some supervised algorithms that have been used previously to construct classification models between different injury and non-injury classes in biomarker studies include linear discriminant analysis (LDA) [14], logistic regression analysis (Logit) [22], and k-nearest-neighbors (KNN) [34]. LDA and logit algorithms are more common and advantageous than KNN algorithms because they are easier to be implemented and interpreted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that supervised classifier algorithms perform better than unsupervised methods when development of predictive models of injury and future outcome is the goal rather than identification of hidden patterns within the dataset [33]. Some supervised algorithms that have been used previously to construct classification models between different injury and non-injury classes in biomarker studies include linear discriminant analysis (LDA) [14], logistic regression analysis (Logit) [22], and k-nearest-neighbors (KNN) [34]. LDA and logit algorithms are more common and advantageous than KNN algorithms because they are easier to be implemented and interpreted.…”
Section: Resultsmentioning
confidence: 99%
“…These biochemical and metabolomic alterations first appear in the brain tissue and then, by crossing a number of barriers, manifest in biofluids such as cerebrospinal fluid (CSF), blood, saliva and urine [1][2][3][4][5][6][7][8][9][10][11][12]. Therefore, biofluids contain valuable information about the occurrence and progression of TBI and thus recently have been explored as a source for potential biomarkers to diagnose TBI, as well as to assess its severity, monitor its progression, predict patient outcomes, and determine the effectiveness of therapeutic interventions [1,4,5,[9][10][11][13][14][15][16][17][18][19]. The use of serum biomarkers has greatly contributed to improved diagnostic and therapeutic methods in fields such as hematology, cardiology, oncology, and infectious disease [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a 2018 study, Ko et al (176) identified a miRNA based panel biomarker to diagnose TBI, both in a mouse model and human TBI. MiRNAs associated with EVs positive for GluR2 (an AMPA receptor subunit) were isolated from plasma of mice exposed to blast overpressure injury.…”
Section: Extracellular Vesicle Mirnasmentioning
confidence: 99%
“…They also found that the expression of miR-21 in the brain was primarily localized in neurons adjacent the lesion site and microglia present near these miR-21-expressing neurons were activated [ 139 ]. Interestingly, Han et al found that miR-21-5p was elevated in neurons after TBI [ 140 ]. Recently the same group demonstrated that Exos derived from neurons of TBI with highly expressed miR-21-5p, injected into the mouse induced the polarization of M1 microglia.…”
Section: The Emerging Role Of Exosomal Mirna In the Diagnosis And mentioning
confidence: 99%